Overview of energy consumption in Brazilian iron ore production in the Quadrilátero Ferrífero - Vasconcelos, Joao Antonio; Gomes de Jesus, Renata; de Souza Santos, Yolacir Carlos (Latin American Journal of Energy Research, 2022)
The Brazil stands out in the production of iron ore, which demands large amounts of energy inputs in the production stages. The main energy sources in mining are electricity, diesel oil, explosives and natural gas or heavy oil (pelletizing), which demand high levels of energy. In the last decade there has been a tendency for the iron content in mineral reserves to decrease, which makes it increasingly necessary to search for more efficient processes and lower energy consumption in the production chain, in order to reduce operational costs and carbon dioxide emissions into the atmosphere. Thus, this project aimed to evaluate the behavior in the last decade of the global energy consumption in the production of iron ore in a mining complex formed by several mines and plants, located in the Quadrilátero Ferrífero, Minas Gerais, Brazil. To this end, we used desk research with a non-probabilistic quantitative approach based on the data available in the Annual Mining Reports and then evaluated the measures for energy efficiency improvements, according to the existing literature. The results showed that ore characteristics and grades, proper planning of mining, the ratio of waste rock to ore, the complexity of the mill processes, and transportation alternatives can be determinants of energy consumption. In general, it is concluded that one should always seek an integration with energy management and efficiency in the different production stages, in order to obtain operational optimization, resource savings and socio-environmental gains.
Keywords: : mine, iron ore, energy management, energy efficiency